PENGARUH MOTIVASI, KEPUASAN KERJA, DAN KOMITMEN ORGANISASIONAL TERHADAP KINERJA KARYAWAN (Studi Kasus PT. PLN Sektor Mahakam Samarinda) - Suwardi Gunawan; Ratna Sari Sirajang; Dutho Suh Utomo (Jurnal Ilmiah Dinamika Teknik, 2020)
Electricity is the impetus of economic activity and improving the quality of human life. PT PLN (Persero) Sektor Mahakam Samarinda as the company that is supply the electricity who keep trying to provide the best service to their customer, so its demanding to every elements which is involved in improving the performance. The aim this study was to know about the influence of motivation of variable, job satisfaction, and organizational commitment to the employee’s performance at PT PLN (Persero) Sektor Mahakam, Samarinda. The respondent of this study was the employees of 4 power plants in Samarinda and Kutai Kartanegara which is owned by PT PLN (Persero), there are 132 respondents. The data was collected by using questionnaire method and giving the question list or questionnaire to the respondents directly. The data analysis technic in this study was using analysis SEM (structural equation modelling) that is operated by AMOS 22 program. The results of this study showed that the variable of job satisfaction was not influential to the employee’s performance (CR = -1,216; P = 0,224), the variable of motivation was influential to the employee’s performance (CR = 2,412; P = 0,016), the variable of job satisfaction was not influential to the organizational commitment (CR = 0,868; P = 0,385), the variable of motivation was influential to the organizational commitment (CR = 2,022; P = 0,043), and the variable of organizational commitment was not influential to the employee’s performance (CR = -1,102; P = 0,271) Keywords: Performance, Organizational Commitment, Job Satisfaction, and Motivation